Unraveling the interactive effect of opaque2 and waxy1 genes on kernel nutritional qualities and physical properties in maize (Zea mays L.) - Subhra J. Mishra; Ikkurti Gopinath; Vignesh Muthusamy; Rajkumar U. Zunjare; Gulab Chand; Arun K. T. Venkatesh; Elangbam L. Devi; Konsam Sarika; Zahirul A. Talukder; Jitender Kumar; Firoz Hossain (Scientific Reports)
Abstract The mutant waxy allele (wx1) is responsible for increased amylopectin in maize starch, with a wide range of food and industrial applications. The amino acid profile of waxy maize resembles normal maize, making it particularly deficient in lysine and tryptophan. Therefore, the present study explored the combined effects of genes governing carbohydrate and protein composition on nutritional profile and kernel physical properties by crossing Quality Protein Maize (QPM) (o2o2/wx1 + wx1 + ) and waxy (o2 + o2 + /wx1wx1) parents. Selected homozygous genotypic classes from F2 populations showed that double mutants (o2o2/wx1wx1) had the highest amount of lysine (mean: 0.396%), tryptophan (mean: 0.099%), and amylopectin (mean: 98.56%) than respective single mutants (o2o2/wx1 + wx1 + : lysine: 0.338%, tryptophan: 0.083%, amylopectin: 74.66%; o2 + o2 + /wx1wx1: lysine: 0.223%, tryptophan: 0.040%, amylopectin: 95.21%). The wx1 was found to impart an enhanced effect on the lysine and tryptophan, while o2 complemented enhanced amylopectin content in the population in the o2 + o2 + and wx1 + wx1 + genotypic background, respectively, besides o2o2wx1wx1 genotypes. The pattern of kernel hardness observed based on average genotypic values was o2 + o2 + /wx1 + wx1 + (401.28 N) < o2 + o2 + /wx1wx1 (330.99 N) < o2o2/wx1wx1 (304.28 N) < o2o2/wx1 + wx1 + (210.96 N). Therefore, with the distinctive effects of wx1 and o2, improving lysine, tryptophan, and amylopectin while maintaining kernel hardness is feasible while breeding for o2o2/wx1wx1 germplasm and enhancing the utilization spectrum of waxy maize.